2005
DOI: 10.1007/s00467-004-1696-5
|View full text |Cite
|
Sign up to set email alerts
|

Rapid development of glomerular injury and renal failure in mice lacking p53R2

Abstract: The Rrm2b gene encodes p53R2, a catalytic subunit of ribonucleotide reductase that is required for DNA repair. Embryonic stem (ES) cells containing a retroviral insertion in the Rrm2b locus were used to generate mutant mice. Analysis of kidney RNA from Rrm2b (-/-) mice showed that the retroviral insertion disrupted expression of Rrm2b transcripts. Rrm2b (-/-) pups were represented at the expected Mendelian ratios at 10-12 days of age and grew normally past weaning. Mice failed to thrive after 6 weeks of age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 29 publications
(38 reference statements)
1
34
0
Order By: Relevance
“…Methods for gene trapping in ES cells, identification of trapped genes by using OmniBank sequence tags (OSTs), and characterization of retroviral gene-trap vector insertion points are published in refs. [23][24][25][26]. OmniBank ES cell clone OST352973 was used to generate Angptl4 Ϫ/Ϫ mice as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…Methods for gene trapping in ES cells, identification of trapped genes by using OmniBank sequence tags (OSTs), and characterization of retroviral gene-trap vector insertion points are published in refs. [23][24][25][26]. OmniBank ES cell clone OST352973 was used to generate Angptl4 Ϫ/Ϫ mice as described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…The p53 protein homolog p73 has also been shown to induce p53R2 expression after DNA damage (4). Knock-out mice lacking a functional p53R2 gene died from severe renal failure by the age of 14 weeks (17,18).It has been shown that DNA damage in budding yeast activates the Mec1/Rad53 kinases (homologs to ATR and Chk1 in mammalian cells (19)), which lead to transcriptional up-regulation of the RNR genes and degradation of the small RNR inhibitor protein Sml1 (20 -23). As a consequence, RNR activity increases, and the dNTP pools are elevated 7-fold in logarithmically growing cells, which is about 4-fold higher than the maximal level of dNTP pools during the S phase (24).…”
mentioning
confidence: 99%
“…The p53 protein homolog p73 has also been shown to induce p53R2 expression after DNA damage (4). Knock-out mice lacking a functional p53R2 gene died from severe renal failure by the age of 14 weeks (17,18).…”
mentioning
confidence: 99%
“…p53R2 is a p53-inducible RR and participates in p53-induced DNA repair by supplying dNTP in response to various types of DNA damage (Nakano et al, 2000;Tanaka et al, 2000;Hakansson et al, 2006). The exact physiological function of p53R2 is not known, but it is essential for cell survival, because mice lacking functional p53R2 apparently grow normally up to 6 weeks but then die from kidney failure (Kimura et al, 2003;Powell et al, 2005). In addition to being a component of the RR holoenzymes, R1, R2 and p53R2 subunits seem to play an important role in determining the malignant potential of tumor cells.…”
Section: Discussionmentioning
confidence: 99%